STRATEGI PENGELOLA PASAR TRADISIONAL DALAM MENGHADAPI KEBERADAAN SUPER MARKET (ANALISIS ETIKA BISNIS DALAM ISLAM) - Eko Cahyono; Saifuddin (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This research focuses on management strategies in traditional markets. The purpose of this research is to find out the strategies that will be applied by traditional markets in facing the existence of modern markets (super markets). This management is to increase the purchasing power of consumers who have started to switch to modern markets. The object of this research is the trader's strategy in market management. The research method used is qualitative with a field study research approach. The results of this study are that the products offered by traditional markets are different from other products and provide benefits for users so that users can attract consumers' purchasing power. The price offered is also affordable, this is also one of the attractions of consumers to help determine their choices in shopping.